A Literature Review On Indonesian Banking Architecture (IBA) - Sutardi, Fitrah Diraya; Yuniar, Awaliyah Fadya; Sidik, Nur Halimah; Riyandi, Riyandi; Lastari, Devi Suci; Sitinjak, Moses Aprildo Jerico; Manda, Gusganda Suria (Peneliti.net, 2025)
The Indonesian Banking Architecture (IBA) is a strategic policy launched by Bank Indonesia in 2004 to build a healthy, efficient, and resilient national banking system in the face of global economic dynamics. Over the past two decades, IBA has been a guideline for transforming Indonesia's banking sector. The program is designed to strengthen the national banking structure through policies, including banking consolidation, capital consolidation, technological infrastructure development, and improved governance and risk management. As a result of this policy, the quantity of banks in Indonesia has decreased, which is in line with the strengthening of capital quality, thus creating a more solid and integrated banking system. This article explores the benefits of IBA’s implementation for the banking industry in the last two decades. This study utilizes secondary data from related academic research.